Characterization of genetic polymorphisms in Nigerians residing in Guangzhou using massively parallel sequencing. (September 2020) - Wu, Riga; Peng, Dan; Ren, Han; Li, Ran; Li, Haixia; Wang, Nana; Shen, Xuefeng; Huang, Erwen; Zhang, Yinming; Sun, Hongyu
Highlights: A total of 58 STRs and 94 iiSNPs were typed in Nigerians residing in Guangzhou Both targeted region variations and flanking region variations were analyzed The combined match probability of the 27 A-STRs was low at 9.06 × 10 -38 Abstract: African populations exhibit extensive linguistic and cultural diversity but are less studied from a population genetic standpoint. Although much genetic data on admixed African individuals, such as African Americans, have been published, genetic polymorphism data, especially that based on sequence-based typing, are still insufficient in indigenous Africans. In this study, we examined the genetic diversity of 85 Nigerians residing in Guangzhou, China. Forensically relevant genetic markers, including autosomal short tandem repeats (A-STRs), X-chromosomal STRs (X-STRs), Y-chromosomal STRs (Y-STRs), and identity-informative single nucleotide polymorphisms (iiSNPs) were genotyped to uncover the genetic polymorphisms of this population. Sequence-based allelic variations were observed in 22 A-STRs, ten Y-STRs, and four X-STRs. Using massively parallel sequencing (MPS), the allele number increased from 475 length-based alleles to 683 sequence-based alleles. Compared to other populations, the overall observed heterozygosity of the 27 A-STRs was the highest in Nigerians, which reflected the higher genetic diversity of this population. The combined match probability of the 27 A-STRs was low at 9.06 × 10 -38 . When both A-STRs and iiSNPs were considered, the cumulative discrimination power, and combined power of exclusion for duo and trio paternity testing was 1–2.97 × 10 -57, 1–2.20 × 10 -10 and 1–4.61 × 10 -17, respectively, which demonstrated that the STRs and SNPs analyzed here can be applied to forensic investigations. In summary, this study uncovers the genetic features of the Nigerian population and provides valuable frequency data for forensic applications.